The Interpretive Movements of Language and Desire: Engagements of Poetry and Place in Qualitative Research - David Lewkowich (Language and Literacy: A Canadian Educational e-journal, 2010)
In this work, I seize on the movements of language engaged in the confusions of qualitative research. I examine the impressions and effects of a researcher’s desires, in which language serves simultaneously as a point of alienation, and as an imperfect enunciatory tool forever directed at satisfaction. Provoking a haunted analysis of autobiographical place, I also dwell in the poetic influences of topographical reading. The result is a methodological inquiry into the ways we move when we do educational re-search, and the curricular paths that languages help to inscribe in this performance.